Some approaches to developing the central places system in Schleswig-Holstein - Hahne, Ulf (Raumforschung und Raumordnung | Spatial Research and Planning, 1999)
The „central place” concept is employed in all of Germany’s federal states (apart from the city-states) as an instrument to steer state-level regional planning. By comparison with other states, the system in place in Schleswig-Holstein is very broadly recognised and taken into account both for spatial planning and in the context of budget allocations to local authorities. Empirical surveys of actual settlement development reveal that this system promotes future-orientated development in rural areas. There would appear to be a special need to develop the system further in areas characterised by the presence of close linkages between towns and cities and the areas surrounding them. A number of proposals are put forward which will place co-operation between cities and surrounding municipalities on a firmer footing.